Weed Dynamics In No-Till Maize System And Its Management: A Review - Pant, Chudamani; Sah, Shrawan Kumar; Marahatta, Santosh; Dhakal, S (Agronomy Journal of Nepal, 2021)
Among different factors, tillage and weed management are two important factors that influence remarkably the growth and yield of maize. The present review reveals that Echinochloa colona L. is the most dominant weed species with an importance value index (IVI) of 41 followed by Papaver rhoeas L. (32.6), Descurainia Sophia L. (22.27) and Polygonum aviculare L (16.16) in no-till maize. Wider spacing and initial slow growth of maize during the first 3-4 weeks provides enough opportunity for weeds to invade and offer severe competition, resulting in 60-81% in maize yield losses. The shift of the weed population towards perennial was observed under NT. Species like Xanthium strumarium, Solanum nigrum, Euphorbia helioscopia, Convolvulus arvensis, Sorghum halepense, Digitaria sanguinalis, Sonchus oleraceus and Euphorbia vermiculata were associated with no-till Zea mays. The highest weed seed density was found in conservation agriculture practices (no-tillage, no-fertilizer and no-herbicide use) with the highest seed distributed in 0-1 cm depth followed by 1-3 cm depth. Weed control efficiency of Nicosulfuron @0.90 kg/ha was found the highest (98.8%) followed by Atrazine + Tembotrione + Atrazine (@1 kg/ha + 120 g/ha + 0.5 kg/ha) (98.7%) and Tembotrione + atrazine (@ 120 g/ha + 0.5 kg/ha) (96.5%), therefore were very effective in controlling weed in no-till Zea mays.